Biofilm Biology and Engineering of Geobacter and Shewanella spp. for Energy Applications - Hu, Yidan; Wang, Yinghui; Han, Xi; Shan, Yawei; Li, Feng; Shi, Liang (Frontiers in Bioengineering and Biotechnology, 2021)
Geobacter and Shewanella spp. were discovered in late 1980s as dissimilatory metal-reducing microorganisms that can transfer electrons from cytoplasmic respiratory oxidation reactions to external metal-containing minerals. In addition to mineral-based electron acceptors, Geobacter and Shewanella spp. also can transfer electrons to electrodes. The microorganisms that have abilities to transfer electrons to electrodes are known as exoelectrogens. Because of their remarkable abilities of electron transfer, Geobacter and Shewanella spp. have been the two most well studied groups of exoelectrogens. They are widely used in bioelectrochemical systems (BESs) for various biotechnological applications, such as bioelectricity generation via microbial fuel cells. These applications mostly associate with Geobacter and Shewanella biofilms grown on the surfaces of electrodes. Geobacter and Shewanella biofilms are electrically conductive, which is conferred by matrix-associated electroactive components such as c-type cytochromes and electrically conductive nanowires. The thickness and electroactivity of Geobacter and Shewanella biofilms have a significant impact on electron transfer efficiency in BESs. In this review, we first briefly discuss the roles of planktonic and biofilm-forming Geobacter and Shewanella cells in BESs, and then review biofilm biology with the focus on biofilm development, biofilm matrix, heterogeneity in biofilm and signaling regulatory systems mediating formation of Geobacter and Shewanella biofilms. Finally, we discuss strategies of Geobacter and Shewanella biofilm engineering for improving electron transfer efficiency to obtain enhanced BES performance.